COST PROMOTION DAN PENINGKATAN MARKET SHARE PRODUK TABUNGAN PT. BANK MANDIRI (PERSERO) TBK - Haslindah Haslindah (AL-IQTISHAD, 2020)
AbstrackThis study aims to determine whether there is significant influence between costs to increase Market Share Promotion Savings Products PT. Bank Mandiri (Persero) Tbk. Hypothesis testing to see the realtionship or influence Promotion of Market Share increased PT. Bank Mandiri (Persero) Tbk, done by statistical tests Simple Linear Regression Analysis using Statistical Product and Service Solution (SPSS)16. Statistical test results show promotional cost significantly influence the in crease Market Share Sarvings products at PT. Bank Mandiri (Perseero) Tbk. With a coefficient of 0399, meaning that if the cost of promotions rose 1 points then Market Share Savings products at PT. Bank Mandiri (Persero) Tbk will increase by 0399.Kata Kunci : Promosi, Market Share, PT. Bank Mandiri (Persero) Tbk.